2011
DOI: 10.1002/pmic.201000564
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of canola leaves under salinity stress

Abstract: Although canola is a moderately salt-tolerant species, its growth, seed yield, and oil production are markedly reduced under salt stress, particularly during the early vegetative growth stage. To identify the mechanisms of salt responsiveness in canola, the proteins expressed in the second and third newly developed leaves of salt-tolerant, Hyola 308, and salt-sensitive, Sarigol, cultivars were analyzed. Plants were exposed to 0, 175, and 350 mM NaCl during the vegetative stage. An increase in the Na content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 42 publications
7
93
1
1
Order By: Relevance
“…The increase in soluble protein contents in rice plants by exogenous application of plant growth regulators under water stress may be due to their possible involvement in water stress adaptation process (Tuna et al, 2008). The plants produce proteins which are involved in decontamination of free radicals and thus play important role in plants adaptation under stress conditions (Witzel et al, 2009;Bandehagh et al, 2011). It is well documented that the cellular proteins contents of plants pass through variations under stress conditions (Guo and Song, 2009;Mohammadkhani and Heidari, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in soluble protein contents in rice plants by exogenous application of plant growth regulators under water stress may be due to their possible involvement in water stress adaptation process (Tuna et al, 2008). The plants produce proteins which are involved in decontamination of free radicals and thus play important role in plants adaptation under stress conditions (Witzel et al, 2009;Bandehagh et al, 2011). It is well documented that the cellular proteins contents of plants pass through variations under stress conditions (Guo and Song, 2009;Mohammadkhani and Heidari, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It also makes the investigation of dynamic expression of proteins possible (Guo et al, 2012). Bandehagh et al (2011), studied salt tolerance in canola by extracting proteins from seedling´s leaves. The results indicated that Na accumulation in sensitive cultivars is higher than tolerant cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…There, reduction in abundance of RubisCo large/small subunit, chloroplast precursor (OEE), Oxygen-evolving enhancer protein 2, carbonic anhydrases as well as Rubisco's activity leads to short assimilation. Fall in assimilation has been reported for many glycophyte plants subjected to salinity stress (Aghaei, 2008; Pang et al, 2010;Sobhanian et al, 2010;Chatlopadhyay 2011 andBandehagh et al, 2011). However, in some sensitive plants, including durum wheat, an increase in activity of RubisCo is thought to be a response rendered to support the carboxylase activities of RubisCo (Caruso et al, 2008).…”
Section: Protein Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gadallah [18] found that salinity decreased the soluble proteins content of Vicia faba L. exposed to salt stress. Under salinity the plants produce stress-responsive proteins that are involved in detoxification of ROS and thus play a role in adaptation to stress [6]. According to the plant species or cultivar the stress conditions resulted in changes in soluble protein contents due to cell structural modifications [49].…”
Section: Acta Biologica Hungarica 66 2015mentioning
confidence: 99%